Comparatively investigation of real MSW and biomass tar treatment by a rotating gliding arc. (15th August 2021) - Kong, Xiangzhi; Wu, Angjian; Fu, Siming; Xu, Ruiyang; Zhao, Yucheng; Li, Xiaodong; Yan, Jianhua
Highlights: Real MSW and biomass tar directly from the gasification plants are treated using the rotating gliding arc plasma. The destruction efficiency and products distribution of major components from both MSW and biomass tar treatment are compared in terms of vapor concentration, CO2 concentration and the discharge current. Rotating gliding arc can achieve over 90% destruction efficiency for real tar treatment. The order of destruction efficiency of the components tends to be η (Monocyclic species) > η (Bicyclic species) > η (Tricyclic species) Abstract: Effective tar removal is the bottleneck in gasification application with municipal solid waste (MSW) and biomass as feedstocks. Herein, a rotating gliding arc plasma reactor equipped with a specific designed swirling generator and pre-heating systems is firstly proposed to treat real tar rather than tar surrogates. The composition of MSW and biomass tar is comparatively analyzed. The influence of vapor concentration, CO2 concentration and the discharge current on the destruction efficiency and distribution of gas products are systematically emphasized. The destruction efficiency of major components from both MSW and biomass tar can reach up to over 90%. The order of destruction efficiency of the components tends to be η (Monocyclic species) > η (Bicyclic species) > η (Tricyclic species). Amongst, species with oxygen-containing functional group such as –OH is prone to be destructed compared with those aromatic hydrocarbon species. Similar changing trend of MSW and biomass tar destruction efficiency dependent on operating parameters is detected, with slight differences attributed to the differences of element and group content.